SUSTAINABILITY VALUES: A COMPREHENSIVE FRAMEWORK FOR ADULT EDUCATION - Ahrens, Andreas; Dzerviniks, Jānis; Skromule, Ilze; Usca, Svetlana; Blazulioniene, Silva; Zascerinska, Jelena; Kavolius, Robertas; Hognadottir, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Sustainability means prioritising the needs of all life forms and of the planet by ensuring that human activity does not exceed planetary boundaries. Adult education plays an important role in empowering adult learners to foster sustainability and its values. Sustainability competence is guided by sustainability values. Competence is considered as an educational category, thereby adult education is aimed at infusing sustainability values into adult learning. However, sustainability values are an under-explored area in scientific literature. Only sustainability values for children have been listed. The aim of this research is to analyse sustainability values in scientific literature underpinning the creation of a framework of sustainability values to be embedded into adult education. The exploratory research is employed in this work as there is no well-defined framework of sustainability values. Scientific literature review as a method of investigation is deployed. Obtained data are processed via content analysis. A novel framework of inter-related sustainability values was created. The novel framework is based on the principles of interconnectedness and interdependency of sustainability values. The framework categorizes sustainability values from the external and internal perspectives. A new research question has been formulated: What are modern methods to foster adult learners’ sustainability values?